2016
DOI: 10.7554/elife.16793
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic shifts in endogenous microbiota impede tissue regeneration via distinct activation of TAK1/MKK/p38

Abstract: The interrelationship between endogenous microbiota, the immune system, and tissue regeneration is an area of intense research due to its potential therapeutic applications. We investigated this relationship in Schmidtea mediterranea, a model organism capable of regenerating any and all of its adult tissues. Microbiome characterization revealed a high Bacteroidetes to Proteobacteria ratio in healthy animals. Perturbations eliciting an expansion of Proteobacteria coincided with ectopic lesions and tissue degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 75 publications
7
93
0
1
Order By: Relevance
“…Recent work with the planarian S. mediterranea found similar bacterial types as we detected in D. japonica, and blooms of Proteobacteria in the S. mediterranea microbiome were associated with tissue degeneration, while high abundances of Bacteroidetes, including Chryseobacterium and Pedobacter, were associated with healthy animals (Arnold et al, 2016). Work is ongoing to analyze the functional significance of the D. japonica microbiome, but we predict that shifts in the ratio of Proteobacteria and Bacteroidetes may also impact D. japonica growth and development.…”
Section: Ta B L Esupporting
confidence: 80%
“…Recent work with the planarian S. mediterranea found similar bacterial types as we detected in D. japonica, and blooms of Proteobacteria in the S. mediterranea microbiome were associated with tissue degeneration, while high abundances of Bacteroidetes, including Chryseobacterium and Pedobacter, were associated with healthy animals (Arnold et al, 2016). Work is ongoing to analyze the functional significance of the D. japonica microbiome, but we predict that shifts in the ratio of Proteobacteria and Bacteroidetes may also impact D. japonica growth and development.…”
Section: Ta B L Esupporting
confidence: 80%
“…After animal dissociation, cells associated with mCherry/mScarlet-labelled E. coli or with bioparticles had similar complex cytoplasmic appearances, with numerous intracellular bodies observable by Nomarski microscopy (Figure S7H-L). Using an endogenous bacterial-level assay [30], foxF-1 RNAi animals had significantly more bacteria than controls (Figure S7M). This could reflect intestinal and/or cathepsin + cell dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Three or four animals were pooled and homogenized in 100 μl of deionized water. 25 μl was then plated on LB agar without any antibiotics and incubated in the dark at room temperature [30]. A water control was also plated, but no bacterial colonies grew on those plates at the time of bacterial colony counting.…”
Section: Star Methodsmentioning
confidence: 99%
“…These studies revealed that gut microbiota can have remote benefits on the wound healing process. Arnold et al () used a planarium ( Schmidtea mediterranea ) as a model organism in order to study the relationship between gut microbiota and tissue regeneration. Schmidtea mediterranea can regenerate and replace any of its either damaged or lost tissues.…”
Section: The Remote Effect Of the Gut Microbiota On Tissue Healing Anmentioning
confidence: 99%